Merchandising and DSR development program of Nestle Bangladesh Ltd.: merchandising and DSR development program - Awal, Rakib Bin (BRAC University, 2016)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2015.